Apreciacíon personal del hombre como antidoto contra crisis .contemporánea de la identidad de la “generación Y” (net-generación) - Babiński, Jarosław (Warszawskie Studia Teologiczne, 2018)
„Generation Y” is a term proposed among others by Zygmunt Bauman to characterize the youngest generation of contemporary societies, largely shaped by postmodernism. Postmodernist world of chaotic difference, temporary character, and uncertainty has significant effects on a person who is spilt over to no identity or many different identities and becomes in her life the tool and consumer without personality. In this context, the identity is losing sustainability and human person is losing the identity uniqueness. Awareness of subjectivity, identity and development of personal and spiritual spheres of life, as well as a reference to fundamental human values can bring solution for the postmodern person. Such development is possible when at the starting point we consider human person as a whole and unity. It cannot be limited to scientific, fragmented, and reduced to the material dimension of human existence. Life without its fundamental spiritual values loses not only its meaning but leads to self-destruction. The way to find the meaning and value of human life, as well as its dignity, is a return to classic solutions philosophy that recognizes the man as a person.